Serum Potassium Impaction in Children with Gastroenteritis at Emergency Department (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Gastroenteritis is one of the most common gastrointestinal system diseases and is associated with substantial morbidity and mortality…A viral pathogen is a common cause in children, but other pathogens, like bacteria, parasites may be causes…The cornerstone of treatment are oral rehydration solution ( ORS ), IV – fluid therapy, correction of electrolytes disturbances, especially ( hypokalemia )that is associated with more hospital – time admission and complications, like generalized weakness and lethargy, paralytic ileus…So the aim of a study is to estimate the prevalence of hypokalemia in children between ( 1 – 5 years old ) who are suffered from acute gastroenteritis and their complications…It’s a prospective clinical study, enrolled ( 153 patients ) from 15th / January / 2023 till 30th / December/ 2023 at Al- Khansaa Teaching Hospital / Mosul city / Iraq…And is included patients between 1 – 5 years old who are suffering from gastroenteritis and admitted to ER department for less than 24 hours, then to Pediatric – Medical ward and their serum potassium level less than 3.5 mmol / L...My excluding criteria were children out of a range of age - group, diarrhea for more than 1 week duration, bloody – diarrhea, parenteral diarrhea, like ( pneumonia, UTI), any nutritional diseases, like marasmus, glycogen storage diseases….etc. and any congenital – GIT system anomalies …I was depending on the proper history taking from a relative to a patient, serial - physical examination on the included patient at ER – department and Pediatric – Medical Ward, serial serum potassium level measurements with proper follow up for any complications that are occurred due to a hypokalemia…A total of 153 patients, with 93 male and 60 female ( ratio 1.2 : 1 ) and a majority of them were mature – born children from urban areas…  61 patients were complicated with hypokalemia and 92 are not, of those are complicated with a hypokalemia were 21 with mild degree, 23 with a moderate degree and 17 with a severe one…According to their complaints, were 61 with a diarrhea only and 27 with a vomiting only, and 65 with both..According to a degree of dehydration, were 72 with a moderate dehydration, and 79 with a severe one…Regarding the UOP, were 11 with a good UOP, 79 with a poor UOP, 63 with a fair UOP…Finally, regarding the complications, were 10 with a generalized weakness and 8 with a paralytic ileus…..